2021
DOI: 10.1186/s13027-021-00388-x
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 quantitative real time PCR and viral loads analysis among asymptomatic and symptomatic patients: an observational study on an outbreak in two nursing facilities in Campania Region (Southern Italy)

Abstract: Background In December 2019 an outbreak of Severe Acute Respiratory Syndrome Coronavirus 2 was first observed in Wuhan, China. The virus has spread rapidly throughout the world creating a pandemic scenario. Several risk factors have been identified, such as age, sex, concomitant diseases as well as viral load. A key point is the role of asymptomatic people in spreading SARS-CoV-2. An observational study in Southern Italy was conducted in order to elucidate the possible role of asymptomatic indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 25 publications
1
8
1
Order By: Relevance
“…We found that the mean and median Ct values were significantly lower among symptomatic than asymptomatic cases, indicating that, on average, viral loads are higher in those with symptoms. This finding contrasts with previous studies demonstrating either no difference in the mean Ct value by symptom status, or lower average Ct values from asymptomatic cases; however, their sample sizes were much smaller (n = 48 to 213 infections) and represent single regional sites [ 37 39 ]. Conversely, we captured Ct values for 7571 positive tests (including repeat tests for the same infection) across a large geographic region (i.e., United States).…”
Section: Discussioncontrasting
confidence: 90%
“…We found that the mean and median Ct values were significantly lower among symptomatic than asymptomatic cases, indicating that, on average, viral loads are higher in those with symptoms. This finding contrasts with previous studies demonstrating either no difference in the mean Ct value by symptom status, or lower average Ct values from asymptomatic cases; however, their sample sizes were much smaller (n = 48 to 213 infections) and represent single regional sites [ 37 39 ]. Conversely, we captured Ct values for 7571 positive tests (including repeat tests for the same infection) across a large geographic region (i.e., United States).…”
Section: Discussioncontrasting
confidence: 90%
“…Only 22 of 130 studies reported the median or mean age [ 38 , 47 , 70 , 76 , 77 , 83 , 85 , 95 , 99 , 119 121 , 124 , 126 , 128 , 133 , 134 , 139 , 143 , 146 , 152 , 164 ] and only 5 studies included children only [ 65 , 67 , 110 , 115 , 118 ]. Only 31 studies reported the sex of people with asymptomatic SARS-CoV-2 ( Table 1 and S2 Table ) [ 38 , 47 , 51 , 53 , 70 , 71 , 75 , 76 , 83 , 85 , 95 , 99 , 107 , 119 122 , 124 , 126 , 128 , 133 , 134 , 139 , 143 , 146 , 147 , 150 , …”
Section: Resultsmentioning
confidence: 99%
“…Amongst all 130 included studies, 88 studies used more than one method of follow-up to ascertain asymptomatic status (Table 1, S2 Table). Only 22 of 130 studies reported the median or mean age [38,47,70,76,77,83,85,95,99,119-121,124,126,128,133,134,139,143,146,152,164] and only five studies included children only [65,67,110,115,118]. Only 31 studies reported the sex of people with asymptomatic SARS-CoV-2 (Table 1, S2 Table) [38,47,51,53,70,71,75,76,83,85,95,99,107,119-122,124,126,128,133,134,139,143,146,147,150,153,158,162,164].…”
Section: Resultsmentioning
confidence: 99%
“…Only 22 of 130 studies reported the median or mean age [38,47,70,76,77,83,85,95,99,119-121,124,126,128,133,134,139,143,146,152,164] and only five studies included children only [65,67,110,115,118]. Only 31 studies reported the sex of people with asymptomatic SARS-CoV-2 (Table 1, S2 Table) [38,47,51,53,70,71,75,76,83,85,95,99,107,119-122,124,126,128,133,134,139,143,146,147,150,153,158,162,164]. The types of included studies changed across the five versions of the review.…”
Section: Resultsmentioning
confidence: 99%